2019
DOI: 10.24988/ije.2019342801
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on The Social Acceptance of Nuclear Energy: A Case Study on University Students

Abstract: In this study, the causal relationships between the factors related to nuclear energy acceptance and the sensitivity of young generations to nuclear energy are examined with structural equation model. The data obtained by the questionnaire applied to 521 students studying at the faculties of the Kütahya Dumlupınar University were analyzed. The students were asked the questions related to the latent variables which are perceived benefits of energy supply, perceived environmental benefits, risk perception, trust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Thus, the authors suggested that emphasizing the energy supply security benefits of NPT in communications with university students in China could effectively ensure its acceptance among this stakeholder group. Similar findings were reported by Yildiz and Erkan [57], using survey data on 521 Turkish university students to investigate the causal influence of determinant factors of NPT acceptance and sensitivity among Turkish youths. Relying on the evidence from studies using the theory of planned behavior in the United States, Craig and Sayers [58] reported young millennial risk perceptions and awareness of local clean energy initiatives, environmental orientation, and messaging to influence their attitudes toward federal clean energy policies.…”
Section: Previous Studies Of Npt Attitude and Acceptancesupporting
confidence: 80%
“…Thus, the authors suggested that emphasizing the energy supply security benefits of NPT in communications with university students in China could effectively ensure its acceptance among this stakeholder group. Similar findings were reported by Yildiz and Erkan [57], using survey data on 521 Turkish university students to investigate the causal influence of determinant factors of NPT acceptance and sensitivity among Turkish youths. Relying on the evidence from studies using the theory of planned behavior in the United States, Craig and Sayers [58] reported young millennial risk perceptions and awareness of local clean energy initiatives, environmental orientation, and messaging to influence their attitudes toward federal clean energy policies.…”
Section: Previous Studies Of Npt Attitude and Acceptancesupporting
confidence: 80%